Inside and outside shareholders and monitoring: evidence from developing country - Mustapha, Mazlina; Che Ahmad, Ayoib (Virtus Interpress, 2010)
This paper tests the effect of managerial (inside) and block-holders (outside) ownership in relation to agency theory in Malaysian business environment. This study tests the agency relationship in different culture and social contact and provides evidence whether agency theory in non-western organizations have equal impact in Asian organizations. Consistent with agency theory and the convergence of interest hypothesis, managerial ownership (insiders) in Malaysia indicate a negative relationship with the demand for monitoring. This finding may be due to the fact that as the managers are also the owners, there is less conflict, less information asymmetry and less hierarchical organization structure in the companies, which lead to lower monitoring costs. However, another ownership structure, outside block-holders appear to demand more monitoring. This positive relationship may be explained by their effort to compensate their lack of involvement in the daily transactions and internal decisions of the company, especially in the concentrated business environment in the country.